Talk FK Becoming an Effective Researcher - Mritha, Ramalingam (Faculty of Computing, 2021)
PEKAN, 29 July 2021 - A Talk on Becoming an Effective Researcher: Grant Application and Management was organized by FK staff Club, KESUKOMP and conducted by Ts. Dr. Syafiq Fauzi Kamarulzaman, Senior Lecturer, FK on 29 July 2021.